Lobectomy Procedure in Reccurent Hemoptysis and History of Tuberculosis Treatment with Suspected Lung Mycosis - Kartikasari, Ulfah; Sugiri, Yani; Bayuadi, Imam; Erawati, Dini; Yudhanto, Hendy (Malang Respiratory Journal, 2022)
Background : Hemoptysis is one of the often symptoms that complained in respiratory disease with fungal Infection. Jakarta reported that prevalency of Invasive Pulmonary aspergillosis is 7,7% and Pneumocystis pneumonia is 14.5%. Lung mycosis is still difficult to diagnosed so the management of therapy is often too late. The risk factors of lung mycosis in these patient are immunocompromised conditions with Diabetes Melitus, history of Tuberculosis treatment and COPD. The diagnosis criteria of systemic/invasive mycosis are proven, probable and possible. Proven criteria diagnosed is based on host factor, clinical finding and mycology whereas possible criteria diagnosed is based on host factor and clinical finding without mycology.Case Report: We report one case at Dr. Saiful Anwar hospital, Man, 43 years old with History of Tuberculosis Treatment and suspected as Lung Mycosis with chef complained hemoptoe recurrent in last 2 months, shortness of breath, cough, right chest pain, fever, night sweating and decrease of body weight 1-2kg in a month. From the physical examination we found percussion dullness and decreased of lung sound in the right upper thorax examination and laboratory results and chest xray there are suspicion of Aspergillosis. The results of XpertMtb/Rif sputum examination obtained that no Mycobacterium tuberculosis, sputum KOH was not found fungus, cytological sputum was obtained as Class II, and in bacterial sputum culture obtained Klebsiella pneumonia. The patient performed a bronchoscopic examination and continued with open thoracotomy surgery and lobectomy.Conclusion: In these patient the diagnosis of lung mycosis with suspicious of Aspergillosis has gone through a multidisciplinary approach covering the pulmonology, radiology, microbiology and anatomical pathology. Collaboration between doctors, researchers, and the pharmaceutical industry is required to resolve the problem of fungal diseases and can increase the profile of these diseases.